The missing prince - Flanagan, John (John Anthony) (Ranger's apprentice: the royal ranger, 2020)
Charged by Araluen's King Duncan to covertly rescue the Prince of Gallica from a politically ambitious baron, Will Treaty and his apprentice Maddie take to the road disguised as father and daughter jongleurs.